Online Hospital Medical Dispute Resolution Model To Create Fairness - Hawreyvian Rianda Seputra; Dewi Iryani; Gradios Nyoman Tio Rae (Dinasti Research, 2026)
This study aims to analyze the arrangement and implementation of online medical dispute resolution in hospitals to ensure legal certainty, as well as formulate an ideal form of the resolution model to realize justice in the future. The research method used is normative juridical with a qualitative approach through a statute approach to health regulations and electronic transactions. Legal materials were collected through literature studies at the National Library and analyzed descriptively analytically to answer the complexity of medical disputes in the digital ecosystem. The arrangement for online medical dispute resolution currently still relies on Law Number 17 of 2023 concerning Health, which requires non-litigation mediation as a first step, as well as the ITE Law as the basis for the validity of electronic documents. Implementation in hospitals is still fragmentary through medical committees or internal complaint units that are limited to simple online communication, but do not yet have special regulations for Online Dispute Resolution (ODR) outside the courts that comprehensively regulate mediator standards and data security. The condition of the absence of a standard standard creates legal uncertainty, especially regarding the strength of execution of the results of online mediation agreements. The ideal model of the future requires an integrated ODR platform that includes video mediation features, encrypted medical records, as well as the involvement of a certified neutral mediator who understands health law and professional ethics. This system prioritizes the principle of restorative justice to restore the therapeutic relationship between patients and medical personnel through a transparent, efficient, and accountable process.